(untitled) (Proceedings of the International Conference on Education, 2021)
The study of the development process of China’s information education can find that the technological development represented by information technology has had a positive impact on classroom teaching. Design is an applied discipline. In design teaching, technological progress directly affects discipline development, teaching curriculum design, and classroom teaching management. The evolution of teaching content design is the need to continuously adapt to the changes in the new technological environment, and the design of the teaching process and teaching content should pay more attention to the future. The development of education in the future is an issue that we need to study. As the development process of online education, the development of design disciplines also shows that design and technological development are in an integrated relationship, and the influence of technological progress on design education is an interdisciplinary influence. Teaching content design is not only the application of new technology, but also the process of self-improvement, iteration and progress of design education, and ultimately serves the main body of teaching, teachers and students